Nrf2 Deficiency Accelerates IL-17-Dependent Neutrophilic Airway Inflammation in Asthmatic Mice - Kenya Kuramoto; Yuko Morishima; Kazufumi Yoshida; Satoshi Ano; Kai Kawashima; Yuki Yabuuchi; Chio Sakai; Sosuke Matsumura; Kengo Nishino; Kai Yazaki; Masashi Matsuyama; Takumi Kiwamoto; et al. (MDPI AG, 2024)
Asthma is a heterogeneous disease that can be broadly classified into type 2, which is primarily steroid-sensitive and eosinophilic, and non-type 2, which is primarily steroid-resistant and neutrophilic. While the mechanisms leading to the development of molecular-targeted therapies for type 2 asthma are being elucidated, much remains to be learned about non-type 2 asthma. To investigate the role of oxidative stress in refractory allergic airway inflammation, we compared asthma models generated by immunizing wild-type and nuclear factor erythroid-2-related factor 2 (Nrf2)-deficient mice with the house dust mite antigen. Both asthma models had similar levels of airway inflammation and hyperresponsiveness, but the Nrf2-deficient mice had increased oxidative stress and exacerbated neutrophilic airway inflammation compared with the wild-type mice. Type 2 cytokines and the expression of GATA3, a transcription factor that is important for Th2 cell differentiation, had decreased in Nrf2-deficient mice compared with the wild-type mice, whereas helper T (Th) 17 cytokines and the expression of RORγt, which is important for Th17 cell differentiation, had increased. Furthermore, the neutrophilic airway inflammation caused by Nrf2 deficiency was ameliorated by interleukin (IL)-17 neutralization. We have concluded that the disruption of the Nrf2-mediated antioxidant defense system contributed to the induction of Th17 differentiation and exacerbated allergic neutrophilic airway inflammation.